Tip growth in plant and fungal cells - Heath, I. Brent (Ian Brent) (Academic Press, 1990)
Tip Growth in Plant and Fungal Cells covers the basis of the cellular processes of tip growing plants. The book discusses the role of cell wall architecture in fungal tip growth generation; the enzymology of tip growth in fungi; and the electrobiology of apical growth. The text also describes the role of calcium ions in tip growth of pollen tubes and moss protonema cells; the role of actin in tip growth; and the significance of microtubules in the organization of the cytoplasm and the regulation of tip growth. The role of the endomembrane system of plants and fungi in surface generation in tip.